Conducting Field Surveys by Studying the Geological and Physical Conditions in Underground Gas Storage Facilities - Aliyeva, O.A. Aliyeva; Аliyev, А.S. (Herald of Azerbaijan Engineering Academy, 2024)
The ways to study the geological and physical conditions of the created underground gas storage have been considired in the article; Information has been provided on conducting laboratory experiments to study the reservoir properties of the formation and the physical properties of the gas, and carried out mining research for determining the parameters of the layer. In operating wells, gas-dynamic research methods in fixed and unstable modes, and in non-working wells, the temperature regime of the reservoir have been studied. A method for determining the minimum depth of gas storage has been proposed, taking into account the formation pressure, rock pressure and hydraulic fracturing pressure of the formation.